Changes in the health status of patients with complicated forms of colon cancer in the perioperative period - Kubrak, M. A.; Кубрак, Михайло Анатолійович (My University, 2024)
The health status of 71 (100 %) patients treated in the surgical department for complicated forms of colon cancer was analyzed according to the CR-POSSUM scale. At the stage of hospitalization, the average score for the physiological subscale (PS) was 10.62 ± 3.04 points, and for the surgical subscale (SS) - 10.82 ± 2.78 points. The risk of mortality was 6.40 (3.50; 19.10) %. According to the results of reassessment one day after the intervention, the mean score for PS was 11.73 ± 3.07 points, T = 87.00; p ˂ 0.0001. The score for SS was 10.81 ± 2.67 points, T = 2.00; p = 0.5930. The risk of mortality was 11.60 (4.80; 21.20) %, T = 55.00; p ˂ 0.0001. Before discharge, the mean score for PS was 10.63 ± 2.91 points, T = 370.00; p = 0.3082. For SS, the score was 10.74 ± 2.66 points, T = 2.00; p = 0.4660. The risk of mortality was 8.10 (3.40; 16.30) %, T = 345.00; p = 0.2679. Thus, in patients with complicated forms of colorectal cancer, the health status significantly worsens one day after surgery according to the PS of the CR-POSSUM scale (p ˂ 0.0001), which leads to an increased risk of postoperative mortality in patients in this category (р ˂ 0,0001).
Keywords: cancer; colon; complications; diagnosis; prognostic scales; CR-POSSUM